Process-driven SOA patterns for aligning business and IT - Hentrich, Carsten; Zdun, Uwe. (Boca Raton, Fla. : Auerbach Publications, 2012)
"This book provides guidance on how to design and build software architectures that follow principles of business-IT alignment. The authors illustrate the design process step-by-step, using proven patterns that address complex business/technical scenarios, where integrated concepts of SOA, Business Process Management, and event-driven architectures are required. Providing a hands-on guide to process-driven SOA, the text describes how to manage the complexity of business-aligned IT architecture with examples and industry cases"--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Service-oriented architecture (Computer science); Electronic books